Optic Nerve Sheath Diameter Ultrasound Evaluation in Intensive Care Unit: Possible Role and Clinical Aspects in Neurological Critical Patients' Daily Monitoring. (21st March 2017) - Toscano, M.; Spadetta, G.; Pulitano, P.; Rocco, M.; Di Piero, V.; Mecarelli, O.; Vicenzini, E.
Abstract : Background . The increase of the optic nerve sheath diameter (ONSD) is a reliable, noninvasive sonographic marker of intracranial hypertension. Aim of the study was to demonstrate the efficacy of ONSD evaluation, when monitoring neurocritical patients, to early identify malignant intracranial hypertension in patients with brain death (BD). Methods . Data from ultrasound ONSD evaluation have been retrospectively analyzed in 21 sedated critical patients with neurological diseases who, during their clinical course, developed BD. 31 nonneurological controls were used for standard ONSD reference. Results . Patients with neurological diseases, before BD, showed higher ONSD values than control group (CTRL: RT 0.45 ± 0.03  cm; LT 0.45 ± 0.02  cm; pre-BD: RT 0.54 ± 0.02  cm; LT 0.55 ± 0.02  cm; p < 0.000 ) even without intracranial hypertension, evaluated with invasive monitoring. ONSD was further significantly markedly increased in respect to the pre-BD evaluation in neurocritical patients after BD, with mean values above 0.7 cm (RT 0.7 ± 0.02  cm; LT 0.71 ± 0.02  cm; p < 0.000 ), with a corresponding dramatic raise in intracranial pressure. Logistic regression analysis showed a strong correlation between ONSD and ICP (R 0, 895, p < 0.001 ). Conclusions . ONSD is a reliable marker of intracranial hypertension, easy to be performed with a minimal training. Routine ONSD daily monitoring could be of help in Intensive Care Units when invasive intracranial pressure monitoring is not available, to early recognize intracranial hypertension and to suspect BD in neurocritical patients.